PENGARUH KREATIVITAS DAN INOVASI PRODUK TERHADAP KEMAJUAN USAHA PADA ROEMAH BROWNIES GEMIRASARY BANDUNG - Iman Sulaeman (Jurnal Penelitian dan Pengabdian Kepada Masyarakat (JPPM), 2021)
This research aims to determine the respondents' responses regarding Creativity, Product Innovation and Business Success, as well as to determine the magnitude of the influence and Product innovation on the Business Success of Roemah Brownies Gemirasary Bandung in the culinary business, either partially or simultaneously. The population in this study were 102 agent/reseller products from Roemah Brownies Gemirasary, and the number of samples used in this study was the same as the population used.This research method uses descriptive and verification analysis which consists of multiple regression analysis, comparative analysis, and coefficient of determination, as well as hypothesis testing by performing partial t-test and f-test simultaneously.The analysis for the Creativity variable is in the good category, the Product Innovation variable is in the good category, and the Business Success variable is in the very good category. The trial results show that Product Creativity and Innovation are important for Business Success and progress. The results of the hypothesis test prove that there is a difference in the magnitude of the effect on Creativity and Product Innovation of Business Success, either partially or simultaneously.